Magnetoresistance in Ag2+deltaSe with high silver excess - Kreutzbruck, Marc von; Mogwitz, Boris; Gruhl, Friederike; Kienle, L.; Korte, Carsten; Janek, Jürgen; Justus Liebig University Giessen (My University, 2005)
In the present study, we investigated the galvanomagnetic transport properties of polycrystalline AgxSe thin films with silver excess in the range from x=1.5 to 18. The results prove that the silver excess controls the transition from linear magnetoresistance (MR) behavior to the quadratic ordinary MR and the temperature for the metal semiconductor transition. Analyzing the MR effect by Kohler´s rule and comparing the results with the field-free resistivity we observe for 2<x<2.3 a steep rise of the product of mean free path and electron concentration (·n2/3). We interpret this result as a consequence of the percolation of nanoscale silver networks within the semiconducting matrix, i.e., as a consequence of the two-phase character of the system.
Keywords: ddc:540